Can Surgeons Identify ACL Femoral Ridges Landmark and Optimal Tunnel Position? A 3D Model Study - Carl Laverdiere, B.Eng; Drew Schupbach, M.D; Justin Schupbach, M.D; Eric Harvey, B.Sc; Mathieu Boily, M.D; Mark Burman, M.D; Paul A. Martineau, M.D (Elsevier, 2020)
Purpose: To examine the ability of surgeons to identify the osseous landmarks associated with the femoral anterior cruciate ligament (ACL) footprint and locate optimal tunnel placement on 3-dimensional (3D) printed models compared with intraoperative placement. Methods: Twelve sports fellowship-trained orthopaedic surgeons were asked to identify a femoral landmark and an ACL footprint on 10 different 3D printed knees. The 3D models were made based on 20 real patients with different anatomical morphology who later received ACL reconstructive surgery using independent drilling. ImageJ software was used to quantify the measurements, which were then analyzed using descriptive statistics. Results: Overall, none of the surgeons were able to consistently identify the junction of the bony ridges. The mean error per participant ranged from 2.81 to 7.34 mm in the proximal direction (P = 3.30e-05) and from 2.42 to 8.05 mm in the posterior direction (P =4.88e-12). None of the surgeons were able to appropriately identify the center of the femoral footprint on the anatomic 3D models. The difference between the center of the footprint surgeons identified on the 3D model and the tunnel graft location in surgery was significantly different (P = .0046). On average, the magnitude of the error when the surgeons performed the actual surgery was 3.72 ± 2.43 mm, whereas on the 3D models it was 5.82 ± 1.97 mm. Conclusions: Experienced sports fellowship-trained orthopaedic surgeons were unable to correctly identify the junction of the intercondylar and bifurcate ridges and the native ACL footprint on 3D models. Operatively placed tunnels were more accurate implying that looking either through a scope or soft-tissue landmarks play a significant role in surgeons ACL footprint localization. Clinical Relevance: The graft position for ACL reconstruction plays an important role on the kinematics of the knee. This paper shows that soft tissue landmarks are needed to provide reliable reference points for reconstruction.